‘Immanent’ Visibility and ‘Transcendental’ Vision in Japanese Calligraphy - Frențiu, Rodica; Ilis, Florina (Eikón / Imago, 2021)
The premise of the approach in the present paper is the interpretation of Japanese calligraphy as an artistic act and the reception of the calligraphic work of art as the object of the aesthetic relation. By combining the theoretical analysis of the main artistic functions of calligraphy –as both a representative and an expressive art – with the practice of calligraphic art, the present endeavour aims to identify the factual and artistic poetics of this visual (pictorial) and verbal art. As such, our study focuses on the particularities of the calligraphic work of art, given by its means of existence: its object of immanence is concurrently a physical and an ideal object (through its linguistic scriptural contents). In our analysis, the Japanese calligraphic art becomes the object of a reading that exploits the Western and Eastern aesthetic poetic theories, in an attempt to explore this art’s means of existence, functioning, and reception, by revealing its calligraphicity, or its artistic-aesthetic quality. As a reflection on the relation between the image and the word, and on the coherence of the vision triggered by it, based on the characteristics of the visible, our study is an original approach that analyses and interprets the vocabulary and the formal style of a unique artistic field that begins with a linguistic expression, as a means of representation, and culminates with an abstract form of expression, as a means of presentation.